The Role of GKMNU in Reducing Stunting in Glapansari Village, Temanggung: An Analysis of Maqashid al-Shariah - Eka Mahargiani Rokhma; Sumarjoko; Yuda Ardian; Muhammad Zaki Tamami (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study analyzes and evaluates the role of the Nahdlatul Ulama Family Welfare Movement (GKMNU) in Glapansari Village, Temanggung, in addressing the high prevalence of stunting as an effort to achieve the objectives of Maqashid al-Shariah, particularly the protection of future generations (hifz al-nasl). This village was selected because it has the highest stunting rate in Temanggung Regency, which negatively affects children’s growth and development. GKMNU implements a comprehensive program based on religious values, including health and nutrition counseling for pregnant women, education on Islamic parenting patterns, and spiritual strengthening. GKMNU views stunting as a complex issue requiring not only medical intervention but also religious and moral guidance, in line with the principle of protecting offspring within Maqashid al-Shariah. The program also supports the prevention of early marriage by referring to Law No. 16 of 2019, which stipulates the minimum marriage age of 19 years, aiming to protect children and ensure family sustainability. Despite challenges such as limited nutritional awareness, economic constraints, and cultural barriers, the findings emphasize that the synergy of GKMNU as an agent of social change and a facilitator of programs integrating religious values with national legal regulations is essential for creating healthy and dignified families in a sustainable manner. This family-based approach involving all family members is considered effective in preventing stunting.